Linking hydrological connectivity and waterbirds habitat suitability in floodplain Wetlands: Implications for wetland management - Jiakun Teng; Yukou Zhu; Houlang Duan; Xiubo Yu; Shaoxia Xia; Ran Wang; Hui Yang (Ecological Indicators)
Hydrological connectivity is considered a crucial factor in maintaining the biodiversity of wetland waterbirds, but quantifying this relationship remains challenging. This study uses synthetic aperture radar (Sentinel-1 SAR) to efficiently and cost-effectively quantify the number of surface hydrological connectivity days in large floodplain wetlands. Based on waterbird occurrence data from citizen science platforms and The Maximum Entropy Model (MaxEnt) we simulated habitat suitability for different waterbird families in Poyang Lake. Through a coupled analysis of surface hydrological connectivity and habitat suitability, we found that habitat suitability generally increased with connectivity days up to approximately 36–78 days and then declined, except under extreme hydrological conditions. Extreme floods and droughts were associated with reduced habitat suitability. During normal years, habitat suitability showed little difference between controlled sub-lakes and connected sub-lakes. However, in years of flood or drought, the habitat suitability of controlled sub-lakes exceeded that of connected sub-lakes by more than 0.15, indicating that moderate hydrological regulation can mitigate the negative impacts of extreme events on waterbird habitats. This study provides a scientific basis for hydrological management strategies in response to the intensified frequency of extreme hydrological events, aiming to enhance wetland resilience under climate warming.